2019
DOI: 10.1371/journal.pone.0216948
|View full text |Cite|
|
Sign up to set email alerts
|

Molecular mechanisms involved in drug-induced liver injury caused by urate-lowering Chinese herbs: A network pharmacology study and biology experiments

Abstract: As an important part of the comprehensive treatment methods, the urate-lowering Chinese herbs could provide favorable clinical effects on hyperuricemia in its ability to invigorate spleen and remove dampness. Owing to the long-term duration, it brought up the potential adverse reactions (ADRs) and concerns about the drug-induced liver injury from these herbs. To address this problem, the bioinformatics approaches which combined the network pharmacology, computer simulation and molecular biology experiments wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 86 publications
0
16
0
1
Order By: Relevance
“…Thus, formation of quinone methides does not necessarily lead to toxicity in vitro and in vivo . For tetrandrine ( 1 ), other proposed mechanisms might play a more substantial role in toxicity, such as the generation of ROS by CYP2E1 [ 32 ] or the proposed interaction with p38α MAPK, a promotor of inflammatory processes in the liver [ 31 ], or additional effects that remain to be elucidated.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, formation of quinone methides does not necessarily lead to toxicity in vitro and in vivo . For tetrandrine ( 1 ), other proposed mechanisms might play a more substantial role in toxicity, such as the generation of ROS by CYP2E1 [ 32 ] or the proposed interaction with p38α MAPK, a promotor of inflammatory processes in the liver [ 31 ], or additional effects that remain to be elucidated.…”
Section: Resultsmentioning
confidence: 99%
“…The molecular mechanism of tetrandrine-induced toxicity has not been entirely elucidated yet. Li and coworkers [ 31 ] hypothesized that an interaction of tetrandrine with p38α MAPK (mitogen-activated protein kinase) led to liver injury, whereas several other studies suggest the involvement of cytochrome P450 (CYP) enzymes in tetrandrine-induced pulmonary [ 26 , 27 ] and hepatic toxicity [ 32 ]. Qi et al.…”
Section: Introductionmentioning
confidence: 99%
“…The levels of ALT, LDH and ALP increased in the cell culture medium. The mechanism of liver injury may be related to the activation of p38α [ 44 ]. In contrast, idiosyncratic hepatotoxicity (idiopathic DILI) is more common in the clinic and includes immune idiopathic liver injury or inflammatory idiopathic liver injury.…”
Section: Common Drugs and Mechanism Of Dilimentioning
confidence: 99%
“…It has been reported that the alkaloid-rich extract of Evodiae fructus is likely to cause hepatic injury in mice (31). As a major alkaloid compound contained within Evodiae fructus, hepatotoxicity mediated by EVO is induced by enhancing the activity of aspartate aminotransferase, alanine transaminase, lactate dehydrogenase and alkaline phosphatase (32).…”
Section: Introductionmentioning
confidence: 99%